An Improved Method for Extracting Rat Cerebrospinal Fluid with Repeatable Large-Scale Collection - Limei Wang; Wei Yang; Yanhong Ran; Hui Song; Xinxin Yan; Jianmin Guo (Veterinary Sciences)
The aim of this study was to explore an improved method for extracting rat cerebrospinal fluid (CSF), observing the impact on animal health under conditions of large-scale CSF collection and evaluating the feasibility of repeated collections. A total of 20 rats were anesthetized and fixed in a stereotactic frame. A 26G scalp needle, combined with a 1 mL syringe, was used to puncture the atlanto-occipital membrane and collect approximately 170 μL of CSF. CSF was collected twice within 14 days. During the study, animals were monitored daily for food intake, body weight, and hematological parameters, and at the end of the study, histopathological examination was performed. The health of the animals remained good, and repeated CSF collections were feasible. The success rate of the procedure was 100%, with blood contamination in the CSF decreasing from 70% in the first collection to 35% in the second. This technique is convenient, accurate, and suitable for widespread applications.